INFLUENCE OF CFRP ON THE STRENGTH OF RETROFITTED RC BEAMS WITHOUT STIRRUPS - Sengun, Kadir; Arslan, Guray (YILDIZ TECHNICAL UNIV, 2017)
Experimental investigations were conducted to study the behavior of reinforced concrete (RC) and steel fiber reinforced concrete (SFRC) beams retrofitted and strengthened with carbon fiber reinforced polymer (CFRP). Four beams, each of which has a longitudinal reinforcement ratio of 1.34% and a shear span-to-effective depth ratio of 2.5, were tested under mid-span concentrated loads. The specimens consisted of a RC beam, a SFRC beam with 2.0% volume fraction of steel fibers and their companion beams that were loaded up to a certain damage level and then retrofitted with CFRP. The retrofitted beams were intentionally designed to be incompatible with the minimum requirements given by the code for FRP design. However, test results show that the retrofitting with CFRP increases the ductility of RC beams significantly even under such incompatibility.
Keywords: reinforced concrete; beam; carbon fiber reinforced polymer; strength; steel fiber; REINFORCED-CONCRETE BEAMS; Engineering